Adoption and impact of improved bean technologies among the bean growing households in Southern Highlands of Tanzania - Katungi, Enid M.; Letaa, Emmanuel; Kabungo, Catherine; Ndunguru, Agness (International Center for Tropical Agriculture, 2018)
The data are part of the outputs of a survey conducted in Southern Tanzania Highlands between November 2016 and January 2017 by CIAT-PABRA team in collaboration with socio-economics team at Agricultural Research Institute – Uyole. The objective of collecting the data was to assess the adoption of improved bean varieties that have been developed over time by the International Centre for Tropical Agriculture (CIAT) through Pan-African Bean Research Alliance (PABRA) and National Agricultural Research Systems (NARS) in Tanzania and evaluate in ex-post the impacts of their adoption on crop productivity, farm income, crop commercialization and food security. Information on ex-post impacts could provide important lessons for researchers and a basis for development agencies and policy makers when deciding on resource allocation. In line with this point, the study went beyond investigating impacts on the outcomes mentioned above and looked at others indicators of breeding performance and the interventions in seed systems that sought to address challenges of inaccessibility of improved seed by disadvantaged groups such as the poor, women and those in far remote locations. (2016)